Encapsulated Probiotic Microorganisms in Functional Food Products - Starovoitova, S.O.; Kishko, K.M.; Demchenko, O.M.; Bila, V.V.; Старовойтова, С.О.; Кишко, К.М.; Демченко, О.М.; Біла, В.В. (PH "Akademperiodyka" of the NAS of Ukraine, 2023)
Alterations in the composition of the gut microbiota are associated with a wide range of pathologies, including not only inflammatory diseases of the gastrointestinal tract, but also diabetes, obesity, cancer, and diseases of the cardiovascular and central nervous systems. With an imbalance of the microbiota (dysbiosis), there is increased intestinal permeability and a violation of local or systemic immune responses. One of the possible ways to improve intestinal microbiota is the use of dietary supplements and functional food products enriched with highly effective encapsulated probiotic microorganisms, as well as prebiotic compounds. Such products contribute to the restoration of normal intestinal microflora and its integrity, and also indirectly affect the positive outcome in the treatment of many pathological conditions mediated by an imbalance in the intestinal microbiota. Maintaining the activity of probiotics in food carriers or functional food products designed for the prevention and complex therapy of various pathological conditions is important both for the normalization of the intestinal microflora and the health of the body as a whole. In this context, encapsulation is an effective approach to maintain the viability and stability of probiotics under adverse conditions in the gastrointestinal tract and also an effective way to protect from processing conditions, temperature, and transportation. The development of functional nutrition products enriched with highly effective encapsulated probiotic microorganisms is a priority for new research in the field of prevention and treatment in microbiota-targeted therapy. The use of such products is based on the conception of 3p — pathophysiology-based individualized use of probiotics and prebiotics in various pathological conditions mediated by a violation of the qualitative and/or quantitative composition of the intestinal microbiota: implementing a predictive, preventive, and personalized medical approach.